2005
DOI: 10.1007/s00280-005-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Na+, K+-ATPase α1 subunit in the intracellular accumulation of cisplatin

Abstract: The present study was undertaken to identify what regulates intracellular cisplatin (CDDP) accumulation and what changes in membrane fraction of CDDDP-resistant cell line. The CDDP-resistant rat hepatoma cell line, H4-II-E/CDDP, shows a significant decrease in intracellular platinum accumulation compared with parental H4-II-E cells, although there was no difference in the efflux of CDDP between these two cell lines. In this study, we examined the contribution of functional change in active transport to the CDD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…This gender-dependent effect was stimulus specific (13). Furthermore, the Na,K-ATPase alpha 1 subunit expression was decreased following a 24-h exposure to CP, and these results suggest that Na,K-ATPasedependent active transport of CP does not occur in resistant cells, and furthermore, the Na,K-ATPase alpha 1 subunit plays an important role in the transport of cisplatin (14). Data from several studies indicated decreased function of the Na,K-ATPase pump in female heart, ileum, liver, brain tissues as compared to male ones (15).…”
Section: Discussionmentioning
confidence: 64%
“…This gender-dependent effect was stimulus specific (13). Furthermore, the Na,K-ATPase alpha 1 subunit expression was decreased following a 24-h exposure to CP, and these results suggest that Na,K-ATPasedependent active transport of CP does not occur in resistant cells, and furthermore, the Na,K-ATPase alpha 1 subunit plays an important role in the transport of cisplatin (14). Data from several studies indicated decreased function of the Na,K-ATPase pump in female heart, ileum, liver, brain tissues as compared to male ones (15).…”
Section: Discussionmentioning
confidence: 64%
“…As mentioned above, cisplatin ( cis -diaminedichloroplatinum) is also a potent anticancer drug [106-108]. It is well known that cisplatin inhibits Na + ,K + -ATPase, but rather a high cisplatin concentration (280-800 μM) and/or a long period of incubation (60-90 min) was required to obtain about 50% inhibition of enzyme activity.…”
Section: Inhibition Of Na+k+-atpase Activitymentioning
confidence: 99%
“…Rather than competing with the normal substrates for these transporters, it is likely that DDP disables these enzymes by binding to key thiol groups. The ability to bind DDP may underlie the increase in resistance to DDP that is observed after overexpression of some of these enzymes (Kishimoto et al, 2006). It is of substantial interest that DDP-associated nephrotoxicity is accompanied by severe copper deficiency (DeWoskin and Riviere, 1992).…”
Section: Discussionmentioning
confidence: 99%